2012
DOI: 10.1186/1756-0500-5-41
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of the ventral disc of Giardia lamblia

Abstract: BackgroundGiardia lamblia is a multiflagellated protozoan that inhabits the small intestine of vertebrates, causing giardiasis. To colonize the small intestine, the trophozoites form of the parasite remains attached to intestinal epithelial cells by means of cytoskeletal elements that form a structure known as the ventral disc. Previous studies have shown that the ventral disc is made of tubulin and giardins.ResultsTo obtain further information on the composition of the ventral disc, we developed a new protoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…A striking feature of Giardia encystation is disassembly of the adhesive disk [16] . We detected 22 of 38 previously published adhesive disk candidates [64] , [65] , 3 of which (GL50803_101291, 103676 and 13584) were at most 2-fold more abundant at 4hpie ( Table S2 ). This is consistent with previous reports of 2D PAGE analyses showing little change in adhesive disk protein abundance during encystation [16] .…”
Section: Resultsmentioning
confidence: 90%
“…A striking feature of Giardia encystation is disassembly of the adhesive disk [16] . We detected 22 of 38 previously published adhesive disk candidates [64] , [65] , 3 of which (GL50803_101291, 103676 and 13584) were at most 2-fold more abundant at 4hpie ( Table S2 ). This is consistent with previous reports of 2D PAGE analyses showing little change in adhesive disk protein abundance during encystation [16] .…”
Section: Resultsmentioning
confidence: 90%
“…These improvements for in vitro growth occurred within 2 weeks in 106-MtzR, while fluctuations in growth rate requiring higher seeding volumes at passage were observed for 713-MtzR for up to 4 weeks (P8). As both WB-MtzR and 713-MtzR have reduced abundance of beta-giardin and SALP-1 (4410) proteins of the ventral disc [ 58 ], it is possible both lines have lower attachment ( Supplementary Fig. S8 ) due to changes in the structure of the ventral disc and, therefore, lower confluence and slower division.…”
Section: Resultsmentioning
confidence: 99%
“…Palm et al [40] carried out a proteomic analysis of the cytoskeleton preparation and reported the presence of a family of giardins (α-1, β, γ, and δ) and two isoforms of tubulin and a new protein, SALP-1, which is homologous to proteins that participate in the aggregation of striate fibers. Subsequently, a proteomic analysis was carried out by Lourenço et al [41] using a cell fractionation approach. They obtained a highly enriched disk fraction that by SDS-PAGE showed the presence of five predominant bands, ranging from 25 to 58 kDa, as well as some light bands with higher molecular weight.…”
Section: Compositionmentioning
confidence: 99%
“…In recent years, proteomic approaches combined with microscope localization technique were carried out and new disk-associated proteins were identified such as the NIMA-related kinases (Neks), ankyrin repeat domain-containing protein, median body protein, and fungal cell wall protein Mp1p. These proteins have specific sites involved in cell adhesion and TTHERM, a hypothetical protein associated with the microtubule formation in the ciliate Tetrahymena thermophila [26,41]. However, despite the effort that has been made to characterize these structures by several research groups, the specific function of each of these proteins is not yet fully understood.…”
Section: Compositionmentioning
confidence: 99%